2019
DOI: 10.1186/s13037-019-0186-4
|View full text |Cite
|
Sign up to set email alerts
|

Does the time of day in orthopedic trauma surgery affect mortality and complication rates?

Abstract: BackgroundOrthopedic trauma surgery has multiple, both patient-based and surgeon-based risk factors. Evaluating and modifying certain patient safety factors could mitigate some of these risks. This study investigates the influence that the time of day of surgery has on mortality and complication rates.Question/purposeThis study evaluates whether the time of day of orthopedic trauma surgery influences complication or mortality rates.Patients and methodsA prospective Swiss surgical database developed as a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 36 publications
1
32
0
2
Order By: Relevance
“…Beyond the statistical question, this means the number of patients that need to be treated (i.e., switched from a conventional to an ambulatory surgical unit) to avoid one additional failure would be 2.9 (95% CI: 1.4, 7.5). We suggest that operating on ambulatory patients outside of regular hours may increase the postoperative morbidity, as already described for other procedures [15,16].…”
Section: Discussionsupporting
confidence: 54%
“…Beyond the statistical question, this means the number of patients that need to be treated (i.e., switched from a conventional to an ambulatory surgical unit) to avoid one additional failure would be 2.9 (95% CI: 1.4, 7.5). We suggest that operating on ambulatory patients outside of regular hours may increase the postoperative morbidity, as already described for other procedures [15,16].…”
Section: Discussionsupporting
confidence: 54%
“…Multiple studies have shown inferior outcomes for surgical procedures during evening hours. [1][2][3][4] However, findings of increased surgical morbidity and mortality during evening hours are by no means universal, as some data show no difference in outcomes for surgical procedures during evening hours. [5][6][7][8][9] The relevance to the public health community for maintaining patient safety during surgery, despite evening operative hours, cannot be overstated.…”
Section: Introductionmentioning
confidence: 99%
“…al. found that night surgery is less effective than day surgery and morning is better than an afternoon (16). But Montaigne et al found that in cardiac surgery, afternoon surgery is more effective (7).In two independent studies, Kelz et al Found (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%